Professor Stefan Czarnecki - ENGEL, Zbigniew W. (Archives of Acoustics, 2007)
On September 1-st 2007 it would have been 25 years from the death of Professor Stefan Czarnecki, a well-known Polish acoustic engineer. Some of his achievements should be reminded here. First of all, it should be remembered that it was his initiative to organize in Poland conferences on noise reduction and that he was a founder of "Archiwum Akustyki" the journal, which later was changed into "Archives of Acoustics".Current, 14-th International Conference NOISE CONTROL 07 continues works of Stefan Czarnecki. The most important papers from the conference will be published in "Archives of Acoustics".Professor Stefan Czarnecki was born in Warsaw on September 20-th 1925. Since 1945 he studied in the Department of Electrical Engineering of Gdańsk University of Technology. He obtained M.Eng. Diploma in electrical engineering in 1949 after presentation of the thesis "Scaling of dynamic microphones by reciprocity method". He worked for a couple of years in the Central Laboratory of the Polish Radio and in the Warsaw University of Technology. In 1953 he started working in the Institute of Fundamental Technological Research of the Polish Academy of Sciences (IPPT PAN) in Warsaw.